2013
DOI: 10.1080/09658211.2013.800553
|View full text |Cite
|
Sign up to set email alerts
|

Effects of similarity on environmental context cueing

Abstract: Three experiments examined the prediction that context cues which are similar to study contexts can facilitate episodic recall, even if those cues are never seen before the recall test. Environmental context cueing effects have typically produced such small effect sizes that influences of moderating factors, such as the similarity between encoding and retrieval contexts, would be difficult to observe experimentally. Videos of environmental contexts, however, can be used to produce powerful context-dependent me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
48
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(52 citation statements)
references
References 54 publications
4
48
0
Order By: Relevance
“…The context-dependent memory effects seen on the first retrieval practice trial in Exper iments 1-3 of the present study are consistent with the robust effects reported by S. M. Smith and Manzano (2010) and S. M. Smith et al (2014), studies that also used video recordings of environments as contexts. That is, in the three experiments of the present investigation, the original study context was either rein stated (in the constant context conditions) or changed (in the varied context conditions) on the first retrieval practice trial, eliciting reinstated context advantages.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The context-dependent memory effects seen on the first retrieval practice trial in Exper iments 1-3 of the present study are consistent with the robust effects reported by S. M. Smith and Manzano (2010) and S. M. Smith et al (2014), studies that also used video recordings of environments as contexts. That is, in the three experiments of the present investigation, the original study context was either rein stated (in the constant context conditions) or changed (in the varied context conditions) on the first retrieval practice trial, eliciting reinstated context advantages.…”
Section: Discussionsupporting
confidence: 93%
“…Recall of paired associates tested in new contexts that were different from encoding contexts was shown to be worse than recall tested with appropriate encoding contexts reinstated (S. M. Smith et al, 2014). Therefore, retrieval practice in a new context, as in the varied condition, should be more difficult than retrieval practice in the original encoding context.…”
Section: Discussionmentioning
confidence: 90%
“…Ample research has shown that mental reinstatement of a context, typically through the use of visual imagery, aids in the recovery of information that had been acquired in that context. 39,40 By providing potent visual cues to promote context visualization, photographs may accelerate the initial phase of the mental time travel process that is considered to be the hallmark of autobiographical recollection. 1,41,42 Furthermore, camera-based studies typically present participants with multiple images depicting the temporal unfolding of an event, which provides additional contextual information and increases the likelihood of there being sufficient cues for retrieval 43 while easing the demands on the executive system to engage in self-initiated episodic search processes.…”
Section: Figure 2 a Comparison Of Autobiographical Recall In Patientmentioning
confidence: 99%
“…It would be misleading, however, to attribute this trend to differences between incidental and supportive contexts, because the test context in the varied/supportive context condition was conceptually similar to the encoding context. Smith, Handy, Angello, and Manzano (2014) showed that contexts similar to encoding contexts cue recall better than new contexts, but not as well as original encoding contexts. The weaker reinstatement effect with supportive contexts could also explain why the effect of varied supportive contexts was weaker than the effect of varying incidental contexts, because the varied supportive contexts were all conceptually similar to each other.…”
Section: Discussionmentioning
confidence: 97%
“…Studies where recall was better under context-reinstated conditions used various manipulations of environmental contexts, including underwater vs. on dry land (Godden & Baddeley, 1975), different laboratory rooms (McDaniel, Anderson, Einstein, & O'Halloran, 1988;Smith, 1979;Smith, Glenberg, & Bjork, 1978), and videos of environments (Smith, Handy, Angello, & Manzano, 2014;Smith & Manzano, 2010). Although Smith and Vela's meta-analysis (2001) showed that physical environmental manipulations have reliable effects on memory, the average effect size for such studies is modest (d = 0.28); in contrast, context reinstatement effect sizes for videos of environmental contexts are large (d > 1.0).…”
mentioning
confidence: 99%